2015
DOI: 10.1515/prilozi-2015-0068
|View full text |Cite
|
Sign up to set email alerts
|

Etiological Factors in Urgent Gastroduodenal Ulcer

Abstract: The presence of Helicobacter pylori with the urgent gastroduodenal ulcer was exceptionally high, in 89.6% of the duodenal and gastric ulcers. NSAID and aspirin are factors that also influence the etiology of this disease. Smoking is a significant risk factor. Alcohol is less present, but still an important factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Our results are close to those found by Begovic, G. and al. [9] and Camara and al. in Guinea [6] who found an average age of 41 and 43.16 years respectively but discordant with those of Lawson, A. in Togo [3] and Belhadj, H. and al.…”
Section: Discussionmentioning
confidence: 90%
“…Our results are close to those found by Begovic, G. and al. [9] and Camara and al. in Guinea [6] who found an average age of 41 and 43.16 years respectively but discordant with those of Lawson, A. in Togo [3] and Belhadj, H. and al.…”
Section: Discussionmentioning
confidence: 90%
“…73 Further, Begovic, et al found that more than half of ulcer patients enrolled into their study were smokers, and this difference was signi cant when compared to the those who were non-smokers. 72 Levenstein, et al observed that age-, gender-, and socioeconomic status-adjusted associations were signi cant for smoking. 90 Park, Kim, Jung, et al investigated the role of changes in smoking status in risk of gastroduodenal ulcer.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, other studies focused on the percent presentation of risk factors; 72,86 risk by measuring the increase in incidence of the respective disease; [91][92][93]114 the differences in mortality with respect to magnitude of exposure 95 , and utilized a novel predictive model to identify risk factors. 115 Table 1.…”
Section: Methodsmentioning
confidence: 99%